Effect of speciation transformation on the coagulation behavior of Al(13) and Al(13) aggregates - Wu, Xiaohong (Water science and technology : a journal of the International Association on Water Pollution Research, 2009)
Flocculation of kaolin suspension with aluminium fractal polycations was investigated as a function of aluminium concentration and pH. Aluminium flocculants included Al(13) and Al(13) aggregates with OH/Al ratio of 2.6 and 2.8, respectively. The flocculation kinetics and floc size distribution were monitored by light scattering. The characterization of flocculants showed that the tridecatmer Al(13) and bridged [Al(13)](n) with out-sphere structure were the dominant species for all flocculants in a wide pH range. The coagulation results indicated that the pre and in situ-formed [Al(13)](n) play a key role in removing particles. With the increasing concentration of [Al(13)](n), coagulation mechanisms were transformed from charge-neutralization, electro-patch coagulation to bridge-aggregation. Moreover, sweep-flocculation was involved at higher dosage besides other three mechanisms when amorphous aluminium oxides formed. Hence, chemical interaction between particles and flocculants evolved from surface adsorption to surface precipitation for aluminium polycations by virtue of species transformation